Factors Influencing Purchasing Decisions In Green Palace Housing Ponorogo - Riyanto, Muhammad Iqbal (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2025)
Green Palace Housing is located on Jalan Astokoro, Tambakbayan, Ponorogo. The selection of this research location was based on the results of interviews with the developer who stated that Green Palace is a non-subsidized housing, so there are various factors that influence the decision to purchase a unit there. Therefore, the author proposes an initial hypothesis that there are several factors that influence the decision to purchase a unit at Green Palace Housing Ponorogo. This study uses a quantitative approach with a survey method through the distribution of questionnaires. The sampling technique used is total sampling, so the number of respondents in this study was 100 people who are unit owners at Green Palace Housing. The data obtained were analyzed using multiple linear regression with the help of SPSS software version 25. The results of the study showed that the variables of location, building, and environment have a significant effect on purchasing decisions, while the price variable does not have a significant effect on purchasing decisions at Green Palace Housing Ponorogo. Keywords: Building, Price, Environment, Location, Purchase Decision